Two Years After : Saving a Generation - World Bank (Washington, DC: World Bank, 2022)
LAC has endured one of the longest spells of school closures. The region was hit disproportionately hard in health, economic, and educational terms. In the region, an entire generation of students – approximately 170 million – were fully deprived of in-person education for roughly 1 out of 2 effective school days to date. The effects of the pandemic on the education sector of the region have been severe. The incipient recovery must focus on returning to schooling and, especially, recovering and accelerating learning. In a nutshell, this agenda entails the urgent and comprehensive implementation of four commitments: (i) A commitment to place the education recovery at the top of the public agenda; (ii) A commitment to reintegrate all the children that abandoned school and ensure they stay in it; (iii) A commitment to recover lost learning and ensure the socio-emotional well-being of children; (iv) A commitment to value, support and train teachers.